Strategi Fundraising Zakat Pasca Pandemi Covid-19 - Nurhidayat Nurhidayat (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractIn January 2020, the world was rocked by a corona virus outbreak, the virus first appeared in Wuhan City in China. The impact is not only China that feels other countries including Indonesia feel the shake. The impact caused by the corona virus is multidimensional social, economic, political, educational, and health. For the corona virus zakat institution, it has an impact on the collection of zakat. The purpose of this paper is to identify and analyze new strategies in collecting zakat in Indonesia. The approach used in this paper is descriptive qualitative. The main data source of this paper is information in various media about the fundraising strategy of zakat institutions which we limit Baznas, Dompet Dhuafa, Lazismu and Lazisnu. The conclusion of this paper is that zakat institutions in Indonesia (Baznas and LAZ) currently still integrate the collection manually and digitally. Both of these strategies are still a mainstay, it is adjusted to the muzaki segmentation.Keywords: Strategy, Fundraising, Zakat, Post-Pandemic AbstrakBulan Januari 2020, dunia diguncang wabah virus corona, virus tersebut pertama kali muncul di Kota Wuhan China. Dampaknya tidak hanya negara China yang merasakan negara-negara lainpun termasuk Indonesia merasakan guncang tersebut. Dampak yang ditimbulkan virus corona bersifat multidimensional sosial, ekonomi, politik, pendidikan, dan kesehatan. Bagi institusi zakat virus corona ini berdampak terhadap penghimpunan zakat. Oleh sebab itu pasca pandemi institusi zakat harus melakukan inovasi dalam penghimpunan zakat. Tujuan dari tulisan ini adalah untuk mengidentifikasi dan menganalisis bagaimana strategi baru dalam penghimpunan zakat di Indonesia. Pendekatan yang digunakan dalam tulisan ini adalah kualitatif deskriptif. Adapun sumber data utama tulisan ini adalah informasi di berbagai media mengenai strategi fundraising zakat institusi zakat yang kami batasi Baznas, Dompet Dhuafa, Lazismu dan Lazisnu. Kesimpulan dari tulisan ini adalah bahwa institusi zakat di Indonesia (Baznas maupun LAZ) saat ini masih mengintegrasikan penghimpunan secara manual dan digital. Kedua strtategi ini masih menjadi andalan, hal tersebut disesuaikan dengan segmentasi muzaki. Kata Kunci: Strategi, Fundraising, Zakat, Pasca Pandemi